Cancer-associated isoenzyme of serum galactosyltransferase. - Weiser, M M (1976)
Galactosyltransferase activity was assayed in sera from 58 patients with various types of cancer. On discontinuous polyacrylamide gel electrophoresis a slow-moving peak of galactosyltransferase activity (isoenzyme II) was found to be present in the serum of 43 of these patients in addition to the major isoenzyme I. Isoenzyme II was found in only 2 of 39 patients with various nonmalignant disorders and was not detected in the serum of 22 normal control subjects. There was no correlation between the presence of this electrophoretically distinct isoenzyme and total serum galactosyltransferase activity, alkaline phosphatase, levels of carcinoembryonic antigen, or blood type. However, patients with widespread metastases had significantly higher isoenzyme II levels than those with no metastases or with limited local spread. Further studies will be necessary to evaluate the clinical usefulness of this serum galactosyltransferase isoenzyme in the diagnosis and monitoring of patients with neoplastic disease.